A diet rich in Maillard reaction products protects LDL against copper induced oxidation ex vivo, a human intervention trial - Dittrich, R.; Dragonas, C.; Kannenkeril, D.; Hoffmann, I.; Mueller, A.; Beckmann, M.W.; Pischetsrieder, M. (Food research international, 2009)
Maillard reaction products (MRPs) have antioxidative properties in vitro but the influence of a diet rich in MRPs on oxidative damage in vivo remains unknown. In this study, the influence of thermally processed foods rich in MRPs on copper induced oxidation of human low-density lipoprotein (LDL) in vitro was examined. Moreover, oxidative resistance of LDL (OR) in blood plasma of eight healthy subjects was monitored, who consumed diets poor and rich in MRPs in weekly turn for 3 weeks. Dark beer, bread crust, and roasted coffee led to a statistically significant increased OR in vitro compared to pale beer, bread crumb, and raw coffee. The consumption of a diet rich in MRPS significantly increased plasma OR compared to the diet poor in MRPs by 35.5%. This study indicates that thermally processed foods rich in MRPs inhibit the LDL oxidation in vitro and have the ability to reduce oxidative modification of LDL in vivo.